Evaluation of massive MIMO performance in Terms of Spectral Efficiency - Ghenabzia, Mohammed Bachir.; Bekkouche ,Ikram. (University of Eloued جامعة الوادي, 2025)
This master thesis investigates the spectral efficiency performance of communication systems employing Massive MIMO (Multiple-Input Multiple-Output) technology—one of the cornerstone solutions for fifth-generation (5G) networks and a key enabler for future sixth-generation (6G) networks. The primary objective is to analyze the influence of critical system parameters, including the number of base station antennas, channel conditions, precoding techniques, and pilot contamination, on spectral efficiency. To enhance system performance, the roles of advanced signal processing techniques such as beamforming, Zero-Forcing (ZF), Maximum Ratio Transmission (MRT), and Minimum Mean Square Error (MMSE) precoding are explored, alongside the integration of Intelligent Reflecting Surfaces (IRS). Simulation results, based on Rician fading models in MATLAB, demonstrate that increasing the number of antennas significantly boosts spectral efficiency, especially when appropriate precoding methods are employed. However, beyond a certain antenna threshold, performance gains diminish due to residual interference and pilot contamination effects. The findings confirm that while Massive MIMO can substantially increase network capacity and reliability, achieving optimal performance depends on careful resource allocation, interference mitigation, and the use of scalable, low-complexity techniques.Ce mémoire étudie l'efficacité spectrale des systèmes de communication utilisant la technologie Massive MIMO (Multiple-Input Multiple-Output), l'une des solutions phares des réseaux de cinquième génération (5G) et un catalyseur essentiel pour les futurs réseaux de sixième génération (6G). L'objectif principal est d'analyser l'influence de paramètres système critiques, notamment le nombre d'antennes de station de base, les conditions de canal, les techniques de précodage et la contamination du pilote, sur l'efficacité spectrale. Pour améliorer les performances du système, le rôle des techniques avancées de traitement du signal, telles que la formation de faisceaux, le forçage à zéro (ZF), la transmission à rapport maximal (MRT) et le précodage à erreur quadratique moyenne minimale (MMSE), est exploré, ainsi que l'intégration de surfaces réfléchissantes intelligentes (IRS). Les résultats de simulation, basés sur des modèles d'évanouissement Riciens dans MATLAB, démontrent qu'une augmentation du nombre d'antennes améliore significativement l'efficacité spectrale, notamment lorsque des méthodes de précodage appropriées sont utilisées. Cependant, au-delà d'un certain seuil d'antenne, les gains de performance diminuent en raison des interférences résiduelles et des effets de la contamination du pilote. Les résultats confirment que même si le V MIMO massif peut augmenter considérablement la capacité et la fiabilité du réseau, l’obtention de performances optimales dépend d’une allocation rigoureuse des ressources, de l’atténuation des interférences et de l’utilisation de techniques évolutives et peu complexes
Master's thesis in communications
Keywords: Massive MIMO; SE; precoding; pilot contamination